And everything is going fine [videorecording (DVD)] - Soderbergh, Steven, 1963-; Gray, Spalding, 1941-2004 (Criterion collection, 2012)
After the death in 2004 of American theater actor and monologist Spalding Gray, director Steven Soderbergh (Traffic) pieced together a narrative of Gray's life to create the documentary And Everything is Going Fine. Brilliantly and sensitively assembled entirely from footage of Gray, taken from interviews and one-man shows from throughout his career, it is a rich, full portrait, and autobiography of sorts, of a figure who was never less than candid but retained an air of mystery.